Do oculomotor exercises improve balance, dynamic visual acuity and performance in female volleyball players? A randomized controlled clinical trial - Yazgan, Elif Aleyna; Kaya, Pınar (Pamukkale University, 2023)
Athletes must develop not only their physical and motor capabilities but also their visual and perceptual-cognitive skills to support their performance. This study investigated the effects of oculomotor exercises (OMEs) on elite female volleyball players' dynamic visual acuity (DVA), balance, and vertical jump performance (VJP). Fifty-two female volleyball players were allocated to two groups: the intervention group (IG, n=26) that received OMEs twice a day, six days a week for four weeks in addition to their daily training, and the control group (CG, n=26) that, only continued their daily training. All participants were assessed with the Flamingo Balance Test (FBT), Y Balance Test (YBT), Clinical DVA Test, and Vertical Jump Test (VJT) before and after the study. After the study, FBT, DVA, and YBT posteromedial values in IG improved significantly, but VJP did not change. The results for CG showed no improvements. After the study only FBT score differences were found between the groups. OMEs in volleyball players can help to improve balance by improving DVA and balance. Future research should investigate the effects of volleyball-specific visual training on improving performance skills.
Keywords: Athletic Performance; Balance; Visual Acuity; Volleyball